Biomechanics and potential injury mechanisms of wrestling - Jang, T.; Chen, S.; Chang, C.; Fu, Y.; Lu, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Wrestling is one of the oldest and most popular competitive sports in the world. However, knowledge of the biomechanics of wrestling is not well established and the biomechanical risk factors of injuries remain unclear (Boden et al., 2002). The purpose of this study was to investigate the joint kinematics of the lower limbs and the center of pressure (COP) movements in Greco-Roman style (GR) and free style (FS) wrestlers during tackle defense.